A Vascularized Conductive Elastic Patch for the Repair of Infarcted Myocardium through Functional Vascular Anastomoses and Electrical Integration. (2nd February 2022) - Xiong, Weirong; Wang, Xiaoxian; Guan, Haien; Kong, Fanxuan; Xiao, Zhaoming; Jing, Yihan; Cai, Liu; Hou, Honghao; Qiu, Xiaozhong; Wang, Leyu
Abstract: Conductive cardiac patches have been proven to promote angiogenesis in infarcted myocardium; however, their conductive integrity, elasticity, and vascularization potential have not yet been optimized. The prevascularization of conductive elastic cardiac patches could be an effective strategy for building a substantial connection between the patch and the infarcted heart. Here, a coronary artery casting is introduced into a holey graphene oxide/polypyrrole‐incorporated polyhydroxyethyl methacrylate prefabricated gel to form a vascularized conductive elastic patch. The engineered patches are able to rebuild functional vascular anastomoses and provide strong electrical integration with infarcted hearts, resulting in effective myocardial infarction repair in vivo. RNA sequencing analyses further reveal that the conductive elastic patches under dynamic culture conditions upregulated cardiac muscle contraction‐ and ATP biosynthesis‐related mRNA expression in vitro. Together, this study demonstrates that the fabricated patches have versatile conductivity, elasticity, and vascularization properties, and could therefore be a promising candidate for heart repair. Abstract : The integrity of conductivity, elasticity, and full vascularization into a cardiac patch remains challenging. Here, the authors report a vascularized conductive elastic patch and demonstrate its vascular anastomoses and electrical integration with the infarcted heart, resulting in effective repair for myocardial infarction.